Caesalpinia pulcherrima, Calliandra californica, and Justicia specigera: Chemical and environmental regulation of their growth and development - Davison, Elizabeth L., 1947- (The University of Arizona., 1989)
Investigations of three low-water requiring landscape species produced the following results: (1) Although Calliandra californica flowered under photoperiods from 12 to 16 hours, plants produced more elongation under 16 hour days. Plants grew taller and developed greener foliage under irradiances of 600 μmol·m⁻²·s⁻¹. Branching was not stimulated by foliar sprays of BA, PBA, or BA + GA₄₊₇. (2) Caesalpinia pulcherrima increased biomass under 16 hour days, but were stunted and chlorotic under irradiances of 1950 μmol·m⁻²·s⁻¹. Internodal lengths were restricted with drenches of 3.75 mg · pot-1 uniconazole, and plants sprayed with 500 mg·liter⁻¹ PBA developed more axillary branching without negative elongating effects. (3) Justicia specigera gained more height under 12 hour days, and produced greener foliage, more elongation, and faster flowering under irradiances of 600 μmol·m⁻²·s⁻¹. Plants showed restricted internodal elongation and fewer flowers when drenched with 5.0 mg·pot⁻¹ uniconazole, and developed more axillary branching with no detrimental elongation effects when sprayed with 100 mg·liter⁻¹ BA + GA₄₊₇.